Speleogenesis of the Hermannshöhle cave system (Austria): Constraints from 230Th/U-dating and palaeomagnetic analysis - Lukas Plan; Andrea Schober; Denis Scholz; Christoph Spötl; Petr Pruner; Pavel Bosák (International Journal of Speleology, 2015)
Hermannshöhle is a show cave located near Kirchberg/Wechsel in Lower Austria. Together with three nearby and genetically connected caves, it forms the Hermannshöhlen cave system (HHS). With a length of 5 km, the HHS is the longest cave in the Lower Austroalpine unit. It is arranged as an extreme three-dimensional maze on a ground area of 200 x 200 x 82 m. Speleothems are abundant in this cave and represent the focus of this study. Low carbon isotope values indicate the presence of a soil-covered catchment above the HHS during times of speleothem deposition. 28 samples were dated by the 230Th/U-method and, in combination with palaeomagnetic data from a 5 m-high sediment profile, indicate multiple phases of sediment infill and erosion in the HHS. Although parts of the cave system are nowadays located at or below the level of the nearby Rams brook, they fell dry already at least 125 ka ago. The presence of 540 ka-old speleothems in the middle level demonstrate that this level of the HHS is at least about half a million years old, and the upper level is probably considerably older. A direct correlation between the cave and the modern surface morphology is therefore not possible. The observation that the palaeo-drainage direction in the HHS is perpendicular to the modern surface runoff also demonstrates the occurrence of a major reorganisation of the hydrological regime since the formation of the HHS. The new chronological data allow to constrain the evolution of the HHS as well as its catchment. An average valley incision rate of roughly 100 m/Ma was obtained, which is consistent with studies of other regions in the Alps unaffected by the Pleistocene glaciations. The spatial and temporal distribution of the dated speleothems as well as the lack of corroded flowstone indicate a single major speleogenetic period under phreatic conditions and support a continuous lowering of the groundwater table.